Penerapan Big Book Sintaksis Berbasis PBL untuk Meningkatkan Sikap Kritis dan Kemampuan Menulis Kalimat Sederhana Kelas Rendah - Tama, Elvina Prasetia Widya; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Although writing instruction in elementary education has been the focus of numerous prior studies, research specifically exploring the integration of the Problem-Based Learning (PBL) model with Big Book media to enhance critical attitudes and improve capitalization and punctuation skills among lower-grade students remains limited. This study aims to describe the implementation of the PBL model supported by Big Book media, evaluate its effectiveness in fostering critical thinking, and analyze the improvement in writing skills among second-grade students at SDN Mangkang Wetan 03, Semarang. A mixed-methods approach with an embedded concurrent design was employed, involving 25 students selected through purposive sampling. Data were collected through observation, interviews, documentation, field notes, and written tests (pretest and posttest). Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed using N-Gain analysis and descriptive statistics. The results indicate that most students achieved a